TEACHER COMPETENCE AND STUDENT PSYCHOMOTOR EVALUATION: CURRICULUM IMPLEMENTATION IN SCHOOLS - Mayang Purnama (CV. Adiba Aisha Amira, 2024)
This article aims to investigate the relationship between teacher competence and students' psychomotor evaluation in the context of curriculum implementation in schools. A quantitative approach was used to collect data from teachers and students in several schools. The research instruments consisted of questionnaires to measure teachers‘ perceptions of their competencies and observations to assess students’ psychomotor levels. The results showed that teachers‘ competence has a significant influence on students’ psychomotor evaluation. Teachers who have high competence tend to provide more effective teaching, better facilitate students' psychomotor development, and provide more constructive feedback. In addition, it was found that good curriculum implementation can strengthen the relationship between teacher competence and students' psychomotor evaluation. These findings highlight the importance of developing teachers‘competencies in supporting students’ learning, especially in the psychomotor aspect. The practical implications of this study emphasise the need for continuous training and development for teachers to improve their teaching quality and enhance students' psychomotor evaluation.